One‐Step Liquid Metal Transfer Printing: Toward Fabrication of Flexible Electronics on Wide Range of Substrates. Issue 12 (4th September 2018) - Guo, Rui; Tang, Jianbo; Dong, Shijin; Lin, Ju; Wang, Hongzhang; Liu, Jing; Rao, Wei
Abstract: As soft conductive materials with high liquid fluidity, the room‐temperature liquid metal alloys (LMs) offer a superior alternative to the fabrication of flexible electronics. So far, techniques aiming at patterning LMs are seriously limited by the alloy's high surface tension and poor wettability with many substrates. Additionally, LMs based mass production with fast and efficient printing on desired target still encounters tremendous unsolved challenges. Here, a one‐step liquid metal transfer printing method with wide range substrate adaptability, comprising of polymer‐based adhesive glue, its printing machine, the LMs ink, and the soft substrate is presented. It is demonstrated that even on those substrates with weak wettability to LMs, the liquid metal transfer printing still works well to create complex conductive geometries, multilayer circuits, and large‐area conductive patterns with excellent transfer efficiency, facile fabrication process, and remarkable electrical stability, which is beneficial to quickly construct wearable electronics, 3D folding conductive structures, flexible actuators, soft robots, etc. Moreover, its advantages of self‐healing and recyclable ability make the strategy possible to prepare reconfigurable circuits and further reduce the cost of fabrication and environmental pollution. This study suggests an important way for future widespread practices of liquid metal soft functional electronics. Abstract : A one‐step liquid metal transfer printing method for flexible electronics based on adhesion difference of EGaIn on allied substrates is developed. The EGaIn could be adhered to polymethacrylates glue, but not paper. This fabrication method has five advantages: (1) fast fabrication; (2) excellent electrical stability; (3) simple to fabricate multilayer and large‐area circuits; (4) self‐healing ability; (5) reversion of EGaIn.